2021
DOI: 10.1186/s13071-021-04593-w
|View full text |Cite
|
Sign up to set email alerts
|

Susceptible trichostrongyloid species mask presence of benzimidazole-resistant Haemonchus contortus in cattle

Abstract: Background Benzimidazole (BZ) anthelmintics are widely used to control infections with parasitic nematodes, but BZ resistance is an emerging threat among several nematode species infecting humans and animals. In Sudan, BZ-resistant Haemonchus contortus populations were recently reported in goats in South Darfur State. The objective of this study was to collect data regarding the situation of BZ resistance in cattle parasitic nematodes in South Darfur using phenotypic and molecular approaches, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…Initially, the amino acid exchanges F200Y [ 21 , 22 ], F167Y [ 23 , 24 ] and sometimes E198A [ 25 ] were predominantly reported in many resistant parasite populations. Recently, additional exchanges in codons 198, in particular E198L and E198V in resistant strongyle nematodes, have raised attention at least in some geographical regions [ 26 , 27 , 28 , 29 , 30 , 31 ]. Based on the knowledge that these mutations can confer resistance to BZs, epidemiological surveys have been established to rapidly identify BZ-resistant parasite populations, using methods such as pyrosequencing [ 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], droplet digital PCR [ 31 , 40 ] or deep amplicon sequencing [ 29 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the amino acid exchanges F200Y [ 21 , 22 ], F167Y [ 23 , 24 ] and sometimes E198A [ 25 ] were predominantly reported in many resistant parasite populations. Recently, additional exchanges in codons 198, in particular E198L and E198V in resistant strongyle nematodes, have raised attention at least in some geographical regions [ 26 , 27 , 28 , 29 , 30 , 31 ]. Based on the knowledge that these mutations can confer resistance to BZs, epidemiological surveys have been established to rapidly identify BZ-resistant parasite populations, using methods such as pyrosequencing [ 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], droplet digital PCR [ 31 , 40 ] or deep amplicon sequencing [ 29 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mixed-species GIN infections in sheep in Scotland, FECR indicated AE of 65–77%, but Teladorsagia circumcincta dominated post-treatment FEC and was more highly resistant to both BZD and ML than undifferentiated FECR would suggest [ 59 ]. In cattle in Sudan, resistant Haemonchus contortus was found in cattle despite FECR exceeding 95% because of their low abundance relative to other species such as H. placei [ 68 ]. High levels of AR in minority species can therefore be missed by FECRT unless specific identification is included.…”
Section: Parasite Confoundersmentioning
confidence: 99%
“…On the other hand, Soutello et al (2007) detected anthelmintic resistance on only 20% (5/25) of the farms examined, with an average FECR of 75.9%. In Sudan, Mohammedsalih et al (2021) reported that a reduction (< 90%) in the effectiveness of albendazole on bovine gastrointestinal nematodes had occurred.…”
Section: Farmmentioning
confidence: 99%
“…The resistance of bovine gastrointestinal nematodes to most drugs available on the market has become an emerging problem worldwide (O'Shaughnessy et al, 2014;Rose et al, 2015;Berk et al, 2016;Lobayan et al, 2017;Baiak et al, 2019). In several countries, there are high rates of resistance, such as in New Zealand (Leathwick & Luo, 2017), Australia (Bullen et al, 2016), Germany, Belgium and Sweden (Demeler et al, 2009), Sudan (Mohammedsalih et al, 2021), United States (Gasbarre, 2014) and Argentina (Cristel et al, 2017). In Brazil, there have been reports of resistance to benzimidazoles (Ramos et al, 2020;Fávero et al, 2020), macrocyclic lactones (Neves et al, 2014;Borges et al, 2015;Ramos et al, 2020), imidazothiazoles (Neves et al, 2014;Ramos et al, 2020) and salicylanilides (Silva et al, 2017;Ramos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%